Insulin restores renal neprilysin (NEP) and attenuates the shedding of urinary NEP and KIM-1 in diabetic Akita mice - Gill, Rupinder K.; Salem, Esam S. B.; Grobe, Nadja; Elased, Khalid M. (Frontiers in Pharmacology, 2026)
ObjectiveDiabetic kidney disease (DKD) is characterized by dysregulation of the renin-angiotensin system (RAS) and renal tubular injury. We investigated whether insulin treatment preserves renal homeostasis by modulating neprilysin (NEP), arginase-2 (Arg-2), and kidney injury molecule-1 (KIM-1) regulation in type 1 diabetic Akita mice.MethodsDiabetic Akita mice received three subcutaneous sustained-release insulin implants (0.1 U/day) for 16 weeks. Blood measurements and urine collections were performed weekly. Western blot, enzymatic activity assays, and ELISA were used to analyze renal and urinary NEP, KIM-1, and Arg-2.ResultsFull-length immunoreactive NEP (95 kDa) expression and activity were significantly reduced in Akita mice (p < 0.05 vs. wild type [WT] non-diabetic controls) in both kidney and urine. This decrease was found in both young (9-week-old) and older (27-week-old). Novel urinary immunoreactive NEP smaller fragments (70, 50, and 37 kDa) were detected in 27-week-old diabetic Akita mice but absent in non-diabetic controls mice (WT). Insulin treatment normalized hyperglycemia, reduced albuminuria, and decreased glomerular fibrosis. Furthermore, it restored renal and urinary full-length NEP expression (p < 0.05) and increased NEP activity, while reducing NEP fragment shedding. Notably, while Western blot and activity assays demonstrated reduced full-length NEP expression and activity in Akita mice, ELISA revealed a paradoxical increase in urinary NEP concentration, suggesting the detection of inactive smaller urinary NEP fragments in addition to the full-length. Urinary KIM-1 and renal Arg-2 were significantly increased in 27- weeks old diabetic Akita mice, effects that were significantly attenuated by insulin treatment (p < 0.05).ConclusionInsulin therapy protects against diabetic nephropathy by: (i) augmenting renal NEP activity, (ii) reducing Arg-2-mediated injury, and (iii) attenuating tubular damage as evidenced by decreased urinary KIM-1 and NEP fragment shedding. The presence of low-molecular-weight NEP fragments in urine does warrant further investigation into their potential use as biomarkers for tracking the progression of DKD and monitoring the effectiveness of treatments.